The effect of microstructure on the dynamic shock response of 1045 steel. (15th May 2023) - Euser, V.K.; Jones, D.R.; Martinez, D.T.; Valdez, J.A.; Trujillo, C.P.; Cady, C.M.; Fensin, S.J.
Abstract: The effect of microstructure on the shock response of 1045 steel is investigated via plate impact experiments and postmortem characterization. Three unique microstructures are explored: ferrite-pearlite, martensite, and ferrite with spheroidal cementite (i.e. spheroidized). Two spall recovery experiments, at approximate peak pressures of 3.2 and 3.5 GPa, are conducted to assess the Hugoniot elastic limit (HEL), spall strength, and damage morphology of the various microstructures. The ferrite-pearlite and martensite microstructures exhibit continuous yielding at both quasi-static and dynamic rates, while the spheroidized condition displays discontinuous yielding. Discontinuous yielding of the spheroidized microstructure is attributed to a combined low initial dislocation density coupled with a low dislocation nucleation rate. The spall strength of ferrite-pearlite is consistently lower than the spheroidized microstructure, attributed to elongated cementite that is more susceptible to cracking than more spherical cementite precipitates. Despite a high density of boundaries, martensite exhibits the highest spall strength. A large percentage of the boundaries within the martensite microstructure are found to be low energy (i.e. Σ3 or low angle), and are thus less susceptible to spall damage. Overall, the high spall strength of martensite is likely linked to traditional strengthening mechanisms that limit dislocation motion. Graphical abstract: Image, graphical abstract